The Himalayan Conifers II - Puri, G. S.; Gupta, A. C. (Indian Forester, 1951)
Soil profiles on river alluvia from the chir pine, blue pine, blue pine-deodar communities, and on glacial moraines and alluvia from spruce and silver fir communities were studied from the Parbatti and Kulu valleys. The data show a significant correlation between organic matter, nitrogen and Ca content of the humus. Both nitrogen and CaO tend to increase with an increase in organic matter in these soils. The amounts of organic matter, and nitrogen falls considerably in lower layers of the soil. On the basis of pH, nitrogen, organic matter, and Ca the soils studied have been classed into three categories of skeletal, brown earth and podsolized soils and these three types have been found to bear different forest communities. Ph of the soil also shows relationship with forest communities. Broadly speaking spruce and silver fir communities occurring at higher altitudes are found on brown earth soils of low Ph value, high organic matter, high nitrogen and high amounts of Ca. The blue pine-deodar and deodar occurring in medium altitudes are found on podsolized or old brown earth profiles with medium Ph values, low Ca, medium N and medium organic matter content. The chir pine community occuring on lowest altitudes occupies skeletal soils with high Ph, low organic matter, low nitrogen and medium calcium. The high amounts of nitrogen and organic matter in soils at higher altitudes is probably due to low temperature and high amounts of atmospheric moisture under which conditions the decomposition of plant material in soils is inhibited. On the basis of C/N and CaO content of tree litter of conifer and broad-leaved species growing in these forests explanations have been given for differences in Ph and calcium content of these soils. Some remarks have been offered on the problem of conifer regeneration in this area and the necessity of intensive work on management types of Suri has been stressed for this purpose.